Doppler estimation based on linear interpolation for underwater acoustic communication. Issue 9 (22nd April 2022) - Li, Shibao; Wang, PengHao; Wang, Shuqi; Cong, Yujie; Liu, Jianhang; Cui, Xuerong
Abstract: In this article, we develop a Doppler estimation approach based on linear interpolation for underwater acoustic (UWA) OFDM system. Linear interpolation is used to achieve the resampling of the received signal. By interpolating the sampled signal with different compensation factors at the receiving end, the repeating structure of the CP‐OFDM symbol is used to maximize the correlation value at the fixed window to obtain the estimated value of the Doppler factor. The fixed window is determined based on the length of the cyclic prefix and the maximum path delay. In addition, we deduced the expression of the received discrete sequence to perform correlation operations after interpolation, which is the theoretical basis of our proposed algorithm. Moreover, in order to reduce the number of iterations, which means computational complexity in this algorithm, we recommend using the dichotomy to quickly find the maximum correlation value. Simulation proves that the proposed algorithm perform better than other CP‐OFDM‐based time‐domain autocorrelation algorithms. Abstract : In this article, we develop a Doppler estimation approach based on linear interpolation for underwater acoustic (UWA) OFDM system. Linear interpolation is used to achieve the resampling of the received signal. By interpolating the sampled signal with different compensation factors at the receiving end, the repeating structure of the CP‐OFDM symbol is used to maximize the correlation value at the fixed window to obtain the estimated value of the Doppler factor. The fixed window is determined based on the length of the cyclic prefix and the maximum path delay. In addition, we deduced the expression of the received discrete sequence to perform correlation operations after interpolation, which is the theoretical basis of our proposed algorithm. Moreover, in order to reduce the number of iterations, which means computational complexity in this algorithm, we recommend using the dichotomy to quickly find the maximum correlation value. Simulation proves that the proposed algorithm perform better than other CP‐OFDM‐based time‐domain autocorrelation algorithms.